High-thermal-stability cross-linked electro-optical polymer as well as preparation method and application thereof
By conducting cross-linking reactions in electro-photopolymers, a three-dimensional network structure is formed, which solves the problem of electro-optical performance attenuation of traditional electro-photopolymers in high temperature environments, and achieves high thermal stability and long-term electro-optical coefficient stability of the material.
Patent Information
- Application Number
- CN202411924129.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The orderly arrangement of chromophore molecules in high temperature environments will relax, resulting in attenuation of electro-optical properties, limiting the practical application of materials in devices.
By performing cross-linking reactions in electrophotopolymers, a stable three-dimensional network structure is formed, the glass transition temperature of the polymer film is increased, the orientation of chromophores is limited, the nonlinear relaxation of the material is reduced, and the long-term stability of the electro-optical coefficient is improved.
The crosslinking reaction improves the mechanical strength and overall stability of polymer materials, so that the material maintains the stability of electro-optical properties under high temperature environments, and is stable against a variety of chemical substances, and is suitable for various environments.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical materials, and in particular to a high-thermal-stability cross-linked electro-optic polymer and a preparation method and application thereof. Background Art
[0002] As the key core material for the development of high-speed electro-optic modulators, electro-optic polymers have attracted much attention due to their application prospects in the fields of high-speed optical communications, optical computing, phased array radar and sensing. The development of electro-optic polymers with both high electro-optical performance and high thermal stability is of great significance for the development of high-performance and high-reliability devices. However, under high temperature conditions, the ordered arrangement of chromophore molecules in traditional electro-optic polymers will relax to a certain extent, resulting in the attenuation of electro-optical performance. This problem seriously restricts the practical application of materials in devices. Among the organic electro-optical material systems, the most widely studied are host-guest doped electro-optical materials. This system is simple to make, low in cost and has good reproducibility. Commonly used polymers include polymethyl methacrylate and amorphous polycarbonate (APC). Among them, PMMA polymers have better optical transparency, low price, and better adhesion, which is conducive to subsequent device processing, but there is also a problem of low glass transition temperature (Tg), that is, after doping with chromophores, they still show a faster electro-optic coefficient relaxation phenomenon. Summary of the invention
[0003] In order to solve the above problems in the prior art, the present invention provides a cross-linked electro-optic polymer with high thermal stability and a preparation method and application thereof.
[0004] The present invention finds that a cross-linking reaction can form a stable three-dimensional network structure in an electro-optic polymer. Specifically, this network structure can increase the glass transition temperature of the polymer film, and at the same time can limit the orientation of the chromophore, effectively reduce the nonlinear relaxation of the material, and improve the long-term stability of the electro-optic coefficient of the polymer material in this way. In addition, the cross-linking reaction can increase the mechanical strength of the polymer, making the material less likely to deform or be damaged when subjected to external forces, thereby improving the overall stability of the material. The cross-linked polymer is relatively stable to a variety of chemical substances such as water, acid, alkali, and organic solvents. This stability enables the electro-optic polymer to maintain structural integrity and performance in a variety of environments.
[0005] The carbene crosslinking involved in the present invention is applicable to all polymers and chromophore structures containing C-H bonds through the mechanism of activation and insertion of active carbene C-H bonds, which makes the crosslinking process more efficient. Diazo compounds, as precursors of carbene, have more convenient preparation and milder activation conditions (slightly higher than the glass transition temperature of organic materials, and do not require high-temperature thermal initiation), which allows the crosslinking reaction to be carried out simultaneously during the polarization process of organic materials, allowing polymer materials to withstand a larger voltage during the polarization process. The crosslinking reaction can be carried out in an air atmosphere without the need for an inert atmosphere, which reduces the requirements for environmental control and facilitates practical applications. The above advantages have greatly broadened the application research of carbene crosslinking reactions in the field of electro-optical devices of organic electro-optical polymers with high thermal stability.
[0006] Based on this, the present invention has the following technical solutions: In a first aspect, the present invention provides a cross-linked electro-optic polymer, wherein the cross-linked electro-optic polymer comprises a main polymer, the organic chromophore and a solid cross-linking agent, wherein the solid cross-linking agent is a diazo compound.
[0007] Preferably, the diazo compound includes any one or two of the following: .
[0008] Preferably, the organic chromophore includes any one or more of BHG2, JRD1, HJD, F, HLD and CLD:
[0009] In the present invention, the organic chromophore molecule has a D-π-A structure. The present invention finds that the electro-optic polymer containing the above organic chromophore molecule uses a diazo compound as a cross-linking agent to generate active carbenes through a heating effect, which undergo insertion reactions with the CH bonds of the surrounding chromophore molecules and the main polymer chain segments to form a three-dimensional cross-linked network structure, thereby improving the long-term stability of the electro-optic coefficient of the polymer material.
[0010] Preferably, the mass ratio of the organic chromophore to the solid crosslinking agent is (2-10):1.
[0011] Preferably, the main polymer includes one or more of polymethacrylate polymers, polymethacrylic acid copolymer polymers, polystyrene polymers, polycarbonate polymers, polyarylether polymers, and polyimide polymers.
[0012] Preferably, the cross-linked electro-optic polymer comprises the following components in parts by weight: Main polymer 50~80 parts, 20~50 parts of organic chromophore, 5~20 parts of solid crosslinking agent.
[0013] The present invention provides a cross-linked electro-optic polymer containing a diazo compound. The prepared electro-optic polymer uses a diazo compound as a cross-linking agent and a diazo compound as a precursor of carbene, and has more convenient preparation and milder activation conditions (slightly higher than the glass transition temperature of organic materials, and does not require high-temperature thermal initiation). This allows the cross-linking reaction to be carried out synchronously during the polarization process of the organic electro-optic material. The network structure formed by the cross-linking can increase the glass transition temperature of the polymer film, limit the orientation of the chromophore, effectively inhibit the relaxation phenomenon of the electro-optic coefficient of the material, and improve the long-term stability of the electro-optic coefficient of the polymer material.
[0014] In a second aspect, the present invention provides a method for preparing the cross-linked electro-optical polymer, comprising: dissolving the main polymer, the organic chromophore and the solid cross-linking agent in 1,1,2-trichloroethane, filtering and spin-coating the filtrate onto a glass substrate, and performing vacuum drying at room temperature.
[0015] As a preferred embodiment of the present invention, the method for preparing the cross-linked electro-optical polymer comprises: The main polymer is dissolved with 1,1,2-trichloroethane, and then the organic chromophore is added. After being fully dissolved and evenly filtered, a cross-linking agent is added to obtain a mixed solution after dissolution. The mixed solution is spin-coated onto an ITO glass substrate and vacuum-dried at room temperature for 12 to 24 hours to obtain the electro-optical polymer; preferably, the film thickness is 1 to 2 μm.
[0016] After the electro-optic polymer is made into a film, a gold electrode is sputtered and then subjected to electric field polarization to obtain electro-optical properties, and at the same time, cross-linking and curing are carried out at the electric field polarization temperature to obtain an electro-optical film with a high glass transition temperature and a high electro-optical coefficient. The prepared cross-linked electro-optic polymer film is used as an optical material in the development of devices such as electro-optic modulators.
[0017] Preferably, the thickness of the cross-linked electro-optic polymer film obtained by the preparation method of the cross-linked electro-optic polymer is 1-2 μm.
[0018] In a third aspect, the present invention provides an optical material comprising the cross-linked electro-optical polymer.
[0019] In a fourth aspect, the present invention provides an electro-optical modulator comprising the optical material.
[0020] The preparation method of a cross-linked electro-optical polymer containing a diazo compound provided by the present invention is simple and easy, and efficient cross-linking can be obtained by using a small proportion of a cross-linking agent. Thanks to the activation temperature of the cross-linking agent being slightly higher than the glass transition temperature of the polarized polymer material, the electro-optical properties can be obtained by electric field polarization and cross-linking and curing can be carried out at the same time, thereby obtaining an electro-optical film with a high glass transition temperature, high stability and high electro-optical coefficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 This is the H NMR spectrum of the three-branch diazo compound in Example 1 of the present invention.
[0023] Figure 2 This is the DSC graph of the polymer film obtained from JRD1 and PMMA in Comparative Example 1.
[0024] Figure 3 This is the DSC graph of the polymer film obtained from JRD1, PMMA and the cross-linking agent in Example 1.
[0025] Figure 4 This is the DSC graph of the polymer film obtained from JRD1, PMMA and cross-linking agent in Example 2.
[0026] Figure 5 This is the DSC graph of the polymer film obtained from JRD1, PMMA and cross-linking agent in Example 3.
[0027] Figure 6 This is the DSC graph of the polymer film obtained from BHG2, PMMA and cross-linking agent in Example 4.
[0028] Figure 7 The curves showing the change of electro-optic coefficient of the polarized electro-optic polymer films of Comparative Example 1 and Examples 1-4 after long-term heating (500 hours) at 85°C. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.
[0031] Example 1 This embodiment provides a cross-linked electro-optical polymer, and the preparation method thereof includes: 16 mg of polymethyl methacrylate (PMMA) was added to 0.244 mL of 1,1,2-trichloroethane, and stirred for 2 hours until PMMA was completely dissolved. Then, 6.8 mg of JRD1 chromophore was added, and stirred for 1 hour until the chromophore was fully dissolved. Then, 1.6 mg of diazo compound crosslinker was added to obtain a mixed solution of chromophore molecule, PMMA and crosslinker (mass ratio was 3:7:0.7). The obtained mixed solution was filtered with a 0.22 μm syringe filter and then coated on ITO glass by spin coating (controlling the speed at 1000-1200 rpm), and then dried in a vacuum drying oven at 50°C for 24 hours. The thickness of the obtained polymer film was 1.6 μm.
[0032] In this embodiment, the diazo compound cross-linking agent is , the NMR hydrogen spectrum of the diazo compound crosslinker is shown in Figure 1 ; The chromophore is JRD1, and the chemical structure of JRD1 is as follows: .
[0033] Example 2 This embodiment provides a cross-linked electro-optical polymer, and the preparation method thereof includes: 16 mg of polymethyl methacrylate (PMMA) was added to 0.282 mL of 1,1,2-trichloroethane, and stirred for 2 hours until PMMA was completely dissolved. Then, 10.6 mg of JRD1 chromophore was added, and stirred for 1 hour until the chromophore was fully dissolved. Then, 1.6 mg of diazo compound crosslinker was added to obtain a mixed solution of organic second-order nonlinear optical chromophore compound, PMMA and crosslinker (4:6:0.6). The obtained mixed solution was filtered with a 0.22 μm syringe filter and then coated on ITO glass by spin coating (control the speed at 1000-1200 rpm), and then dried in a vacuum drying oven at 50°C for 24 hours. The thickness of the obtained polymer film was 1.8 μm.
[0034] In this embodiment, the diazo compound cross-linking agent is , the chromophore is JRD1.
[0035] Example 3 This embodiment provides a cross-linked electro-optic polymer, and the preparation method thereof is different from that of embodiment 1 only in that the diazo compound cross-linking agent is replaced by an equal amount of .
[0036] Example 4 This embodiment provides a cross-linked electro-optic polymer, and the preparation method thereof is different from that of Embodiment 1 only in that the chromophore JRD1 is replaced by BHG2, and the structural formula of BHG2 is as follows: .
[0037] The synthetic route of BHG2 is as follows: 1) The synthesis of compound 1 shown in formula 1 can be found in the literature (WW Jin, PV Johnston, DLElder, KT Manner, KE Garrett, W. Kaminsky, RM Xu, BH Robinson, LR Dalton, J. Mater. Chem. C 2016, 4, 3119-3124.) 2) Synthesis of compound 2 represented by formula 2 3.85 g (10 mmol) of compound 1, 5.30 g (30 mmol) of p-toluenesulfonyl chloride, and 30 mL of redistilled tetrahydrofuran (THF) were added to a 50 ml glass three-necked flask and dissolved under nitrogen (N 2 ) environment, the reaction system was cooled to 0°C with an ice bath, and triethylamine was added dropwise; after the reaction was carried out for 1 hour, the ice bath equipment was removed, and the system was allowed to continue to react overnight at room temperature; after the reaction was completed, the mixture was poured into 50 mL of deionized water to terminate the reaction, and the organic phase was extracted three times with ethyl acetate and the organic phase was collected; the unreacted p-toluenesulfonyl chloride was washed away with 10% NaOH solution, and the product was dried over anhydrous magnesium sulfate and rotary evaporated to obtain a red solid crude product, namely compound 2, with a yield of 80%.
[0038] 3) Synthesis of compound 3 shown in formula 3 In a 100 ml round-bottom flask, 1.386 g (2 mmol) of compound 2 obtained in step 2), 3.50 g (10 mmol) of fluorene-9-bisphenol, 1.40 g (26 mmol) of anhydrous potassium carbonate and 50 mL of redistilled N,N-dimethylformamide (DMF) were added; the mixture was heated to 100 °C under nitrogen protection for 24 hours. After the reaction was completed, the mixture was poured into 200 mL of deionized water to obtain an orange solution, which was extracted three times with ethyl acetate. The organic phases were combined and washed with saturated sodium chloride solution. The organic phases were dried with anhydrous magnesium sulfate and the organic solvent was removed by rotary evaporation. The residue was separated by column chromatography (with 200-300 mesh silica gel as the stationary phase and a mixture of n-hexane and ethyl acetate as the mobile phase, wherein the volume ratio of n-hexane to ethyl acetate was 1:20). After drying, a red solid was obtained, which was compound 3 with a yield of 52%.
[0039] MS(MALDI-TOF), m / z:1049.47 (M+); 1 H NMR (400 MHz, CDCl 3 ) δ 10.05 (d, J= 8.3 Hz, 1H), 7.96 (s, 1H), 7.71 (d, J = 7.4 Hz, 4H), 7.36–7.28 (m, 10H),7.25–7.20 (m, 5H), 7.04 (dd, J = 20.2, 7.9 Hz, 8H), 6.67 (d, J = 8.4 Hz,11H), 6.31 (d, J = 8.2 Hz, 1H), 4.07 (s, 4H), 3.79 (s, 4H), 3.61 (s, 3H),2.71 (s, 2H), 2.37 (s, 2H), 1.04 (s, 6H). 4) Synthesis of compound 4 represented by formula 4 10.50 g (10 mmol) of compound 3 and 1.66 g (24 mmol) of imidazole were dissolved in 20 mL of DMF and stirred at N 2 Under protection, 3.68 g (24 mmol) of tert-butyldimethylsilyl chloride was slowly added to the mixed solution. After stirring at room temperature for 3 hours, the reaction system was poured into 100 mL of water. The organic phase was extracted with n-hexane, washed with brine, dried over anhydrous magnesium sulfate, and the solvent was removed by rotary evaporation. The crude product was separated by column chromatography (with 200-300 mesh silica gel as the stationary phase and a mixture of ethyl acetate and n-hexane as the mobile phase for gradient elution, wherein the volume ratio of ethyl acetate to n-hexane was 1:15 and gradually increased to 1:10). After drying, a red oily liquid was obtained, which was compound 4 with a yield of 93.1%.
[0040] MS(MALDI-TOF), m / z:1278.6458 (M+); 1 H NMR (400 MHz, CDCl 3 ) δ 10.08 (d, J = 8.3 Hz, 1H), 7.71 (d, J = 7.5 Hz, 4H), 7.33 (dt, J = 14.8, 5.4 Hz, 10H), 7.21(t, J = 7.3 Hz, 5H), 7.05 (dd, J = 13.2, 8.7 Hz, 8H), 6.67 (dd, J = 8.5, 4.9 Hz,11H), 6.33 (d, J = 8.3 Hz, 1H), 4.05 (t, J = 5.6 Hz, 4H), 3.78 (t, J = 5.5 Hz, 4H), 3.64 (s, 3H), 2.72 (s, 2H), 2.37 (s, 2H), 1.05 (s, 6H), 0.95 (s, 18H), 0.15 (s, 12H). 5) Synthesis of BHG2 1.2 mmol of compound 4 obtained in step 4 and 0.45 g (1.4 mmol) of trifluoro-substituted tricyanodihydrofuran (CF 3 -TCF) was dissolved in 20 mL of ultra-dry ethanol and then refluxed at 80 °C for 0.5 h. After the reaction was completed, the solvent was removed by rotary evaporation, and the crude product was separated by column chromatography (the stationary phase was 200-300 mesh silica gel, and the mobile phase was a mixture of ethyl acetate and n-hexane, and the volume ratio of ethyl acetate to n-hexane was increased from 1:10 to 1:5). The solid obtained after drying was the organic second-order nonlinear optical chromophore BHG2 with a D-π-A structure, with a yield of 38.2%.
[0041] MS(MALDI-TOF), m / z:1575.6972 (M+); 1 H NMR (400 MHz, CDCl 3 ) δ 8.00 (t, J =13.3 Hz, 1H), 7.73 (d, J= 7.5 Hz, 4H), 7.54 – 7.48 (m, 5H), 7.40 – 7.29 (m,10H), 7.23 (dd, J = 13.3, 5.7 Hz, 6H), 7.04 (dd, J = 18.4, 8.5 Hz, 8H), 6.81 (d, J = 16.1 Hz, 1H), 6.72 – 6.63 (m, 10H), 6.44 (d, J = 14.7 Hz, 1H), 4.09 (t, J = 5.4Hz, 4H), 3.84 (d, J = 5.1 Hz, 4H), 3.65 (s, 3H), 2.42 (s, 2H), 2.30 (s, 2H), 1.01 (s, 3H), 0.94 (s, 21H), 0.14 (s, 12H). Comparative Example 1 This comparative example provides a cross-linked electro-optical polymer, the preparation method of which comprises: 16 mg of polymethyl methacrylate (PMMA) was added to 0.228 mL of 1,1,2-trichloroethane, stirred for 2 hours until PMMA was completely dissolved, and then 6.8 mg of JRD1 chromophore was added to obtain a mixed solution of chromophore molecules and PMMA (30 wt.% chromophore). The obtained mixed solution was filtered with a 0.22 μm syringe filter and then coated on an ITO glass substrate by spin coating (controlling the speed at 1000-1200 rpm), and then dried in a vacuum drying oven at 50°C for 24 hours. The thickness of the obtained polymer film was 1.6 μm.
[0042] Test Example 1 1) The polymer film obtained by contact polarization of the organic chromophore molecule (JRD1) of Comparative Example 1 and PMMA, the electrode material is gold (Au), the electrode thickness is 50 nm, the polarization temperature is between 95℃ and 105℃, the polarization time is 20 to 30 minutes, and the polarization voltage is controlled at about 150 to 250 V; the electro-optic coefficient (r 33 ) The maximum electro-optic coefficient measured by Teng-man simple reflection method is 180 pm / V@1310 nm; 2) A polymer film obtained from the organic chromophore molecule (JRD1) of Example 1, PMMA and a crosslinking agent, with a film thickness of 1.6 μm, was subjected to a contact electrode polarization process, wherein the electrode material was gold (Au), the electrode thickness was 50 nm, the polarization temperature was between 95°C and 105°C, the polarization time was 20 to 30 minutes, and the polarization voltage was controlled at about 150 to 250 V; the electro-optic coefficient (r33) was measured by the Teng-Man simple reflection method, and the maximum electro-optic coefficient measured was 150 pm / V@1310 nm; 2) The polymer film obtained from the organic chromophore molecule (JRD1) of Example 2, PMMA and a crosslinking agent was subjected to contact polarization, the electrode material was gold (Au), the electrode thickness was 50 nm, the polarization temperature was between 95°C and 105°C, the polarization time was 20 to 30 minutes, and the polarization voltage was controlled at about 150 to 250 V; the electro-optic coefficient (r 33 ) The maximum electro-optic coefficient measured by the Teng-Man simple reflection method is 230 pm / V@1310 nm; 3) The polymer film obtained from the organic chromophore molecule (JRD1) of Example 3, PMMA and a crosslinking agent was subjected to contact polarization, the electrode material was gold (Au), the electrode thickness was 50 nm, the polarization temperature was between 95°C and 105°C, the polarization time was 20 to 30 minutes, and the polarization voltage was controlled at about 150 to 250 V; the electro-optic coefficient (r 33 ) The maximum electro-optic coefficient measured by the Teng-Man simple reflection method is 165 pm / V@1310 nm; 4) The polymer film obtained from the organic chromophore molecule (BHG2) of Example 4, PMMA and a crosslinking agent was subjected to contact polarization, the electrode material was gold (Au), the electrode thickness was 50 nm, the polarization temperature was between 110°C and 125°C, the polarization time was 20 to 30 minutes, and the polarization voltage was controlled at about 150 to 250 V; the electro-optic coefficient (r 33 ) The maximum electro-optic coefficient was measured by the Teng-Man simple reflection method and was 263 pm / V@1310 nm.
[0043] Test Example 2 1) For the polymer film obtained by the organic chromophore molecule (JRD1) of Comparative Example 1 and PMMA, the glass transition temperature (T g ) was tested, and the heating rate was set at 10°C / min in a nitrogen atmosphere, and the curve was as follows Figure 2 As shown; 2) The glass transition temperature (T g ) was tested, and the heating rate was set at 10°C / min in a nitrogen atmosphere, and the curve was as follows Figure 3 As shown; 3) The glass transition temperature (T g ) was tested, and the heating rate was set at 10°C / min in a nitrogen atmosphere, and the curve was as follows Figure 4 As shown; 4) The glass transition temperature (T g ) was tested, and the heating rate was set at 10°C / min in a nitrogen atmosphere, and the curve was as follows Figure 5 As shown; 5) The glass transition temperature (T g ) was tested, and the heating rate was set at 10°C / min in a nitrogen atmosphere, and the curve was as follows Figure 6 shown.
[0044] Test Example 3 The polarized electro-optic polymer films of Comparative Example 1 and Examples 1-4 were heated to 85° C., and the electro-optic coefficients were tested every 12 to 72 hours for 500 hours. The stability curves of the electro-optic properties are shown in FIG. Figure 7 As shown. The electro-optical properties of the cross-linked electro-optic polymer film after polarization have good stability. After heating to 85°C, the electro-optical properties decayed in the first 10 hours, and then the electro-optic coefficient remained basically unchanged. After being placed at 85°C for 500 hours, the electro-optical properties of the material can still be maintained at more than 85% of the initial value (89% and 87%); however, the electro-optical coefficient of the electro-optic polymer film that has not been cross-linked shows poor stability. After heating at 85°C for 24 hours, the electro-optical coefficient drops to 9% of the original value. Therefore, the prepared polarized electro-optic polymer film can be used as an optical material.
[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cross-linked electro-optic polymer, characterized in that The cross-linked electro-optic polymer contains a main polymer, an organic chromophore and a solid cross-linking agent, and the solid cross-linking agent is a diazo compound.
2. The cross-linked electro-optic polymer according to claim 1, characterized in that The diazo compound includes any one or two of the following: 。 3. The cross-linked electro-optic polymer according to claim 1 or 2, characterized in that: The organic chromophore includes any one or more of BHG2, JRD1, HJD, F, HLD and CLD: 。 4. The cross-linked electro-optic polymer according to any one of claims 1 to 3, characterized in that: The mass ratio of the organic chromophore to the solid crosslinking agent is (2-10):
1.
5. The cross-linked electro-optic polymer according to any one of claims 1 to 4, characterized in that: The main polymer includes one or more of polymethacrylate polymers, polymethacrylic acid copolymer polymers, polystyrene polymers, polycarbonate polymers, polyarylether polymers, and polyimide polymers.
6. The cross-linked electro-optic polymer according to any one of claims 1 to 5, characterized in that: The composition comprises the following components in parts by weight: Main polymer 50~80 parts, 20~50 parts of organic chromophore, 5~20 parts of solid crosslinking agent.
7. The method for preparing a cross-linked electro-optical polymer according to any one of claims 1 to 6, characterized in that: include: The main polymer, the organic chromophore and the solid cross-linking agent are dissolved in 1,1,2-trichloroethane, filtered, and then the filtrate is spin-coated on a glass substrate, and vacuum dried at room temperature.
8. The method for preparing a cross-linked electro-optic polymer according to claim 7, characterized in that: The thickness of the cross-linked electro-optic polymer film obtained by the preparation method of the cross-linked electro-optic polymer is 1-2 μm.
9. An optical material, characterized in that: It contains the cross-linked electro-optical polymer described in any one of claims 1 to 6 or the cross-linked electro-optical polymer prepared by the preparation method described in claim 7 or 8.
10. An electro-optic modulator, characterized in that: It contains the optical material according to claim 9.
Citation Information
Patent Citations
Stabilized electro-optic materials and electro-optic devices made therefrom
CN103270135A
Universal cross-linking agent as well as synthesis method and application thereof
CN113336666A
Compound with D-pi-A structure and preparation method and application thereof
CN115260171A
Crosslinkable and crosslinked polymers
US20060047031A1
Nanoengineered organic nonlinear optical glasses
US20090118521A1
Cited By
Polymer cross-linking agent, preparation method thereof and application of polymer cross-linking agent in organic electro-optical material
CN121135943A
Colloidal particle ink composition, colloidal particle pattern formation method, colloidal particle pattern film, and electronic element, each using colloidal particle ink composition
JP2025107989A
Colloidal particle ink composition, method for forming a colloidal particle pattern using the same, colloidal particle pattern film, and electronic element
JP7854078B2